Empowering the Elderly Through a Holistic Approach: Integrating Health Education and Progressive Islamic Values in the 'Aisyiyah Community - Ellyda Septiani Pramita; Triyas Singgih Pambudi (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2026)
The program is purposed to improve health literacy, promote preventive behavior against degenerative diseases, and strengthen the internalization of progressive Islamic values. The methods included interactive health education, basic health screening, and spiritual sessions designed through a participatory approach with community partners. Program evaluation employed a pre–post knowledge test, descriptive analysis of health screening results, and participatory observation to assess changes in participants’ attitudes and engagement. The evaluation results showed an increase in the mean health knowledge score from 56.2 in the pre-test to 74.5 in the post-test, representing a 32.6% improvement. Health screening of 30 participants identified 55% with hypertension, 15% with diabetes, and 45% classified as overweight or obese. In addition to physical health outcomes, participants demonstrated increased spiritual awareness in understanding health as part of religious practice. The program also resulted in the establishment of an Islamic peer support group as a new social structure to ensure program sustainability. This community engagement contributes to a measurable, replicable community-based empowerment model that integrates promotive–preventive health strategies, progressive Islamic spirituality, and the formation of supportive social structures. The findings enrich community engagement practices and the literature in Indonesia by demonstrating that a holistic, participatory approach effectively enhances the physical, psychosocial, and spiritual capacities of elderly women.